APPLICATION OF ALLOYED-DIFFUSED CARBONACEOUS WIRE FOR MODIFYING OF CAST IRON - V. M. Konstantinov; O. E. Lashkevich; M. V. Semenchenko; T. V. Mihajlovskaja (Литьë и металлургия)
The process of modifying of cast iron by diffusingalloyed steel wire is studied. The peculiarities of structure formation of diffused layer at thermal-cyclic treatment of wire are established.